HYPRO-HYPONYMIC RELATIONSHIPS OF KITCHEN UTENSIL NAMES IN ENGLISH - Shakhlo Shukhratovna Uralova (Western European Studies, 2025)
The article investigates hyper–hyponymic relationships in the lexical-semantic field of kitchen utensil names in English. Hypernymy is understood as a genus–species relation between lexemes, where a general concept semantically includes more specific ones. The study demonstrates that kitchen utensil terminology in English is characterized by a multi-level hierarchical structure, in which lexemes function both as hyponyms and hypernyms at different stages. The analysis reveals that the hypernym cooking/kitchen utensils covers a wide range of lexical-semantic groups, including dishes, kitchen utensils, and kitchen appliances and devices. The results confirm that hyper–hyponymic relations play a crucial role in the systematization, classification, and interpretation of lexical units within the semantic field and reflect both linguistic and cultural specificity.
Keywords: hypernymy; hyponymy; semantic hierarchy; kitchen utensils